Convergecast of multi-destinations in Zigbee tree-based wireless sensor network - Juleang, P.; Mitatha, S.; Yupapin, P. P. (My University, 2010)
Multi-destinations in wireless sensor network have extremely benefited for monitoring system. Then, convergecast is a fundamental operation in wireless sensor network. Existing convergecast solution focused on latency and energy consumption. However, a good design should be complaint to standard. This paper proposes convergecast solution of multi-destinations in Zigbee tree-based wireless sensor network and proves that this solution is simulation. Our solution is optimal convergecast of multi-destination in wireless sensor network and using accompany with network's resource for all destinations. Then, our solution is compliant with the low-power design of IEEE 802.15.4. Simulation results show that the proposed solution can indeed achieve convegecast of multi-destinations.